Pedestrian crossing behavior, an observational study in the city of Ushuaia, Argentina - Poó, Fernando Martín (2018)
Objectives: Pedestrian crashes are a critical problem in Latin American countries. However, little research has been published about pedestrians and even less about their behaviors in a naturalistic context. The objective of the present research was to explore risky pedestrian crossing behaviors in traffic intersections in an argentine city (Ushuaia). It is focused in different stages of the crossing process, traffic code violations, and other potentially risky behaviors such as distractions. A high frequency of risky behaviors among pedestrians was expected. Moreover, according to previous findings, it was hypothesized that men and younger pedestrians would show riskier behaviors. Methods: Participants were 802 pedestrians (53.9% females) observed at several intersections (with and without traffic lights) in the city of Ushuaia. Behaviors were codified following a standardized observation protocol. Observers documented information on behavior previous to, during, and after crossing. Gender and age were also registered. Data were gathered through video recording. Frequency analyses of observed behaviors were conducted for the total sample, as well as by gender and by age group. A general crossing risk index was calculated to facilitate comparisons between the genders and age groups. We conducted an analysis of variance to evaluate gender and age differences for this index. Results: A high proportion of risky behaviors were observed among pedestrians. The majority of pedestrian waited in the street (as opposed to on the sidewalk) before crossing, did not comply with traffic lights, or crossed outside the crosswalk. A large number of pedestrians were distracted while crossing. Men presented higher scores on risky behaviors than women. No differences were observed by age group. Conclusions: The high level of risk behaviors during the different stages of street crossing is worrisome and reinforces the idea that pedestrians are responsible for many of the conflicts with motorists. Many of the risky behaviors seem to be associated with gender, which is in line with the previous literature showing more risk behaviors among men than among women. No differences were found for age group. Findings are interpreted considering some features of the Argentine road culture.